Media Ownership and the Meaning of ‘Police’: A Computational Discourse Study in Indonesian News Portals - Fanny Puteri Cahyani; Merry Andriani (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2026)
The representation of the word “polisi” (police), which is initially lexically neutral, can acquire ideological meaning when it appears within media news texts. This study employs a corpus-linguistic approach using collocation and concordance analyses to reveal how linguistic strategies are constructed through patterns of repetition, lexical proximity, and institutional diction preferences used by the media. Data collection and processing were conducted using Visual Studio Code and the AntConc corpus concordance to examine co-occurrence relationships, grammatical patterns, and the semantic prosody associated with the word polisi (police). The research corpus was compiled contrastively of 1930 articles from Indonesian media outlets with differing institutional orientations, based on Benson’s institutional logic, which emphasizes that media operate within the frameworks of institutional interests and the ideologies that shape them. To complement the analysis, this study also employs Ramlan’s syntactic theory to examine the construction of subject–predicate relations and constituent functions within sentences, as well as semantic prosody theory to evaluate the implicit evaluative load behind collocational patterns. The findings indicate that AntaraNews tends to present a more homogeneous and stable representation, constructing the police as an ideal and professional law enforcement institution, whereas Tempo offers a more heterogeneous, critical, and varied representation, particularly in its emphasis on institutional accountability. These differences demonstrate that media are not neutral entities but rather arenas of discourse production that reflect the ideological orientations of their respective institutions.